Copper demand, supply, and associated energy use to 2050. (July 2016) - Elshkaki, Ayman; Graedel, T.E.; Ciacci, Luca; Reck, Barbara K.
Highlights: Four scenarios for copper demand and supply, and the energy required for copper production have been developed. The cumulative demand for copper is expected to exceed its Reserves and Reserve Base in most scenarios by 2050. The supply of metals co-mined with copper will decrease unless their extraction efficiencies from copper ore are substantially increased. Most of the copper producing countries will not be able to sustain their production until 2050. The energy required to produce copper is expected to constitute between 1.0 and 2.4% of the total energy demand by 2050. Abstract: To a set of well-regarded international scenarios (UNEP's GEO-4), we have added consideration of the demand, supply, and energy implications related to copper production and use over the period 2010–2050. To our knowledge, these are the first comprehensive metal supply and demand scenarios to be developed. We find that copper demand increases by between 275 and 350% by 2050, depending on the scenario. The scenario with the highest prospective demand is not Market First (a "business as usual" vision), but Equitability First, a scenario of transition to a world of more equitable values and institutions. These copper demands exceed projected copper mineral resources by mid-century and thereafter. Energy demand for copper production also demonstrates strong increases, rising to as much as 2.4% of projected 2050 overall global energy demand. We investigate possible policy responses to these results, concluding that improving the efficiency of the copper cycle and encouraging the development of copper-free energy distribution on the demand side, and improving copper recycling rates on the supply side are the most promising of the possible options. Improving energy efficiency in primary copper production would lead to a reduction in the energy demand by 0.5% of projected 2050 overall global energy demand. In addition, encouraging the shift towards renewable technologies is important to minimize the impacts associated with copper production.